Sectoral Reallocations, Real Estate Shocks and Productivity Divergence in Europe: a Tale of Three Countries - Thomas Grjebine; Jérôme Héricourt; Fabien Tripier (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
The creation of the European Monetary Union (EMU) in 1999 was expected to become a catalyst for real convergence in Europe. Far from being the case, real divergence increased from the early 1990s as evidenced by low productivity growth in the "periphery" of the Euro area relative to "core" countries. This report investigates the role of sectoral reallocation in this divergence, focusing on three archetypal countries: France, Germany, and Spain. Using the EU-KLEMS database of sectoral Total Factor Productivity (TFP), we first show that sector reallocations have been at the origin of productivity losses in the considered countries and contributed significantly to this divergence. Second, we investigate how the substantially diverging real estate prices between these countries could explain those sectoral reallocations. More specifically, when access to external finance is restricted due to financial frictions, real estate assets may be used as collateral by borrowers to relax these constraints and increase investments. Real estate shocks turn out to be a strong driver of productivity divergence, causing the lag of Spain behind Germany before the Great Recession and that of France afterwards. For comparison purpose, we also shed light on the role of sectoral reallocation in the UK productivity puzzle.
Keywords: 330